Abrogation of KLF5 sensitizes BRCA1-proficient pancreatic cancer to PARP inhibition - Zhang Zheng; Liu Yuxin; Xu Yaolin; Xu Zijin; Jia Jinbin; Jin Yun; Wang Wenquan; Liu Liang (Acta Biochimica et Biophysica Sinica, 2024)
Poly ADP-ribose polymerase (PARP) inhibitor monotherapies are selectively effective in patients with pancreatic, breast, prostate, and ovarian cancers with BRCA1 mutations. Cancer patients with more frequent wild-type BRCA show poor responses to PARP inhibitors. Moreover, patients who are initially sensitive to these inhibitors eventually respond poorly to drugs. In the present study, we discover that abrogation of Kruppel-like factor 5 (KLF5) significantly inhibits homologous recombination, which is the main mechanism for DNA double-stranded repair. Furthermore, the downregulation of KLF5 expression promotes the DNA damage induced by olaparib and significantly reduces the IC50 of the RARP inhibitor in pancreatic cancer cells. Overexpression of BRCA1 reverses the above effects caused by silencing of KLF5. Olaparib combined with a KLF5 inhibitor has an enhanced cytotoxic effect. Mechanistically, we identify BRCA1 as a KLF5 target gene. BRCA1 is positively correlated with KLF5 in PDAC tissue. Our results indicate that inhibition of KLF5 may induce BRCAness in a larger pancreatic cancer subset with proficient BRCA. The combination of KLF5 inhibitors and PARP inhibitors provides a novel treatment strategy to enhance the sensitivity of BRCA1-proficient pancreatic cancer to PARP inhibitors.